2011
DOI: 10.1007/s10585-011-9437-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-receptor tyrosine kinase 2 reaches its lowest expression levels in human breast cancer during regional nodal metastasis

Abstract: Almost half of breast Ductal Carcinoma in situ are likely to remain non threatening in situ lesions with no invasion to the surrounding stroma and no metastases. The majority of focal disruptions in myoepithelial (ME) cell layers indicative of invasion onset were found to be overlying epithelial cell clusters with no or substantially reduced estrogen receptor α (ERα) expression. Here we report the down-regulation of Tyrosine kinase-2 (TYK2) and up-regulation of Strumpellin expression, among other proteins in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In this model of breast cancer, myeloid-derived suppressor cells (MDSCs) seem to be more effective in Tyk2-deficient mice that in wild-type animals. In bioptic material from breast cancer patients TYK2 appeared to be downregulated, hence consistently influencing cell de-differentiation and the initiation of regional metastases 42 . The function of CD4 + T cells, CD8 + T cells an NK cells was not altered in these mice.…”
Section: The Role Of Tyk2 In Cancermentioning
confidence: 86%
“…In this model of breast cancer, myeloid-derived suppressor cells (MDSCs) seem to be more effective in Tyk2-deficient mice that in wild-type animals. In bioptic material from breast cancer patients TYK2 appeared to be downregulated, hence consistently influencing cell de-differentiation and the initiation of regional metastases 42 . The function of CD4 + T cells, CD8 + T cells an NK cells was not altered in these mice.…”
Section: The Role Of Tyk2 In Cancermentioning
confidence: 86%
“…The important role of TYK2 in immune-surveillance is also in line with findings in patients who carry mutated TYK2 alleles which lead to loss of TYK2, lowered TYK2 levels [46], or expression of kinase-inactive TYK2 [47,48,49], and that show primarily immunodeficiencies. Nonetheless, proteomics suggested that low TYK2 facilitates local metastasis in breast cancer [50], and a comprehensive screen for protein tyrosine kinase variants in numerous cancer cell lines identified splice variants that render TYK2 inactive [51]. On a molecular mechanistic level, the cell intrinsic tumor-promoting consequences of low TYK2 or LOF of TYK2 currently remain elusive.…”
Section: Aberrant Expression And/or Activity Of Tyk2 In Cancersmentioning
confidence: 99%
“…This regulatory loop has not yet been studied in the context of carcinogenesis. Furthermore, knockdown of TYK2 reduced migration of breast cancer cell lines [50].…”
Section: Tumor-promoting Activities Of (Hyper-)active Tyk2mentioning
confidence: 99%
“…The ability of DUSP3 to inhibit STAT5 transcriptional activity may have consequences in cancer cell biology, since STAT5 activity is known to promote cancer by transcriptionally regulating genes involved in proliferation and survival [45], therefore loss of DUSP3 activity could possibly result in increased STAT5 activity thereby promoting cancer development. Furthermore, TYK2 has a suggested role in breast cancer metastasis, as analysis of 140 tissue samples from 70 breast cancer patients revealed that TYK2 protein levels are reduced in tumors that have metastasized to the regional lymph nodes [46]. Additionally, knock-down of tyk2 in the MCF10A breast epithelial cell line decreased cell migration and invasion [46].…”
Section: Dusp3/vhrmentioning
confidence: 99%
“…Furthermore, TYK2 has a suggested role in breast cancer metastasis, as analysis of 140 tissue samples from 70 breast cancer patients revealed that TYK2 protein levels are reduced in tumors that have metastasized to the regional lymph nodes [46]. Additionally, knock-down of tyk2 in the MCF10A breast epithelial cell line decreased cell migration and invasion [46]. Whether loss of TYK2 promotes metastasis, migration, and invasion due to reduced DUSP3 activity remains to be determined DUSP3's activity is additionally activated by the pseudokinase, Vaccinia-related kinase 3 (VRK3) [47], whose expression is down-regulated in colorectal cancer [48].…”
Section: Dusp3/vhrmentioning
confidence: 99%